(NkATALITI^ESKAQ AROMATIZACIQ ALIFATI^ESKIH UGLEWODORODOW (B/s - (NiSAGULQNC(B, (NgEORGIJ wA^EEWI^s; (NrOZENGART(B, (NmARK iOSIFOWI^s; (NdUBINSKIJ(B, (N`RIJ gLEBOWI^s; (NpLAT\(B, (NaLXFRED fELIKSOWI^s; (NiN(B-(NT ORGANI^ESKOJ HIMII IM(B. (Nn(B.(Nd(B. (NzELINSKOGOs ((NmOSKWA (B:s (NnAUKA(B,s, 1983)
(NbIBLIOGR(B. 542 (NNAZW(B.s
(Nan sssr(B, (NiN(B-(NT ORGAN(B. (NHIMII IM(B. (Nn(B. (Nd(B. (NzELINSKOGOs
Keywords: (NaROMATIZACIQ KATALITI^ESKAQs; (NuGLEWODORODY ALIFATI^ESKIEs